Emergent bilingual students in secondary school: Along the academic language and literacy continuum. (24th September 2013) - Menken, Kate
<x content-type="archive" xml:space="preserve">Abstract</x> This article offers a critical review of research about emergent bilingual students in secondary school, where the academic demands placed upon them are great, and where instruction typically remains steadfast in its monolingualism. I focus on recent scholarship about the diversity within this student population, and center on 'students with interrupted formal education' (SIFE, new arrivals who have no home language literacy skills or are at the beginning stages of literacy learning) and 'long-term English language learners' (LTELLs, primarily educated in their receiving country yet still eligible for language support services). Little has been published about these students, making this a significant area of inquiry. Moreover, both groups are characterized by poor performance and together illustrate the characteristics of secondary students at various points along an academic language and literacy continuum. While existing research provides important information to help us improve secondary schooling for emergent bilinguals, it has also perpetuated deficit views of these students by focusing solely on their perceived academic shortcomings. Grounded in a new body of research in applied linguistics that examines the students' complex, creative, and dynamic language and literacy practices, I apply a translanguaging lens to critique the positioning of such students as deficient, with implications for research and practice.